Analysis of mechanical properties, microstructure, and distortion of Al6061-T6 alloys plate using GTA and GMA welding process - Suherman, Suherman; Muharnif, Muharnif; Marzuki, Marzuki; Lubis, Yusuf; Pohan, Muhammad Ade syahputra; Aulia, Rakha Ramdan; Ali, Rizki M; Abdullah, Ilmi; Wan Hamzah, Azmi (Politeknik Negeri Lhokseumawe, 2025)
This study compares the effect of filler metal and welding current of gas tungsten arc welding (GTAW) and gas metal arc welding (GMAW) on Aluminium alloy Al6061-T6. Three different filler metals, ER4043, ER4047, and ER5356, were used with the GTAW welding process. The welded joints were created at three different welding currents (120, 130, and 140 A) by the GMAW with filler metals ER5356. Optical and scanning electron microscopy (SEM) is used to analyze the surface fracture of impact test welding joints. The results showed that the GMAW process had the most optimum Ultimate Tensile Strenght (UTS) compared to the GTAW welding joint, especially for welding current 130 A. The impact strength of ER4047 filler metal with the GTAW process is higher than other joints (61 J/cm2). Optimum conditions were obtained by the GMAW welding process using a welding current of 130 A with maximum tensile strength and impact strength of 350 MPa and 53 J/cm2, respectively. SEM analysis showed obtained Mg2Si a globular morphology in ER4047 and ER5356 filler metals, and the dimples fracture is indicated at all joints with the GMAW and GTAW processes. Furthermore, increasing welding current by the GMAW process causes higher angular distortion, reduced vickers hardness but does not significantly affect the weld bead. Overall, the GMAW produces better physical and mechanical properties of weld joint compared to GTAW for all types of filler metals but results in greater angular distortion